Isolation and characterization of thermophilic bacteria producing L-Asparaginase from Malaysia hotspring and enzyme activity using different carbon and nitrogen sources - Jimat, Dzun Noraini; Mohamed, Intan Baizura; Azmi, Azlin Suhaida; Zainudin, Zaki (AENSI, 2015)
Background: L-asparaginase is being applied in medical field as well as food industry. One of the common applications of the enzyme is being an effective antitumor agent for the treatment of acute lymphoblastic leukaemia. Microbial strains that are producing Lasparaginase can be found in many habitats such soil, waste water and hot springs. The continuous studies are essential to discover new microbial sources to obtain high yielding L-asparaginase producing strains that useful for therapeutic and industrial applications. Objective: The purpose of this study is to isolate thermophilic bacteria producing L-asparaginase from Malaysia hotspring and to observe the L-asparaginase activity produced by the isolated strains. The effect of using different carbon and nitrogen sources in M9 medium was studied to determine the best nutrient components which enhanced enzyme activity. Results: The potential strains producing good Lasparaginase activity were identified as Klebsiella pneumoniae.SK1, Cronobacter sakazaaki.SK2, Acinetobacter baumanni.SK3, Actinobacillus capsulatus.SK4, Klebsiella oxytoca.SK5, Cronobacter sakazaaki.SK6 and Pseudomonas resinovorans.SK7 using Biolog GEN III Microplate Identification System. Cronobacter Sakazakii.SK2 shows the highest L-asparaginase activity (0.17±0.0055 U/ml) among others. However, Acinetobacter baumanni.SK3 was selected for further studies because of highly pathogenic Cronobacter sp. All of the isolated bacteria are gram negative bacteria. Most of them are rod shaped bacteria except for Acinetobacter sp. which sphere in shape. All of them are unable to produce indole compound. Most of them show negative in oxidase activity (except Pseudomonas sp.) and positive in reducing nitrate (except Pseudomonas sp.) and catalase activity (except Klebsiella sp.). Lasparaginase activity was high in presence of sucrose (0.149±0.0049 U/ml). Production medium amended with peptone favored maximum enzyme activity (0.0725 ±0.018 U/ml). Conclusion: Sungai Klah Hotspring is one of the potential sources of useful microbial that can be used as a source of bioactive compound like L-asparaginase. It is recommended to enhance or optimize the enzyme production before such new thermophilic bacterial strains could be considered attractive sources to be used in industrial L-asparaginase production.